Programowa niechęć do państwa jako kwintesencja zjawiska identyfikacji narodowej wśród Kurdów tureckich – analiza głównych przejawów nacjonalizmu kurdyjskiego w Turcji - Szkudlarek, Magdalena (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The aim of this article is to present a comprehensive analysis of the phenomenon of Kurdish nationalism and identity in Turkey. An emphasis will be placed on aspects such as the lack of acceptance of Kurdish nationalists for state-oriented attitudes among some Kurds, the lack of acceptance for the Turkish government’s pro-Kurdish decisions and abusing of tragic Turks and Kurds’ past by both sides of the conflict in order to win the propaganda war. The groundless conviction that “Kurdish nationalism” and “ PKK terrorism” is the same thing leads to misunderstanding that terror is the only indication of show ing Kurdish identity. The true complexity of this phenomenon will be presented in this article.